THE MEDIATING ROLE OF OCB IN THE RELATIONSHIP BETWEEN COMMITMENT, SATISFACTION, AND PERFORMANCE - Albert Budiyanto (jfpublisher, 2025)
The present inquiry endeavors to examine the extent to which organizational commitment and job satisfaction influence employee performance, designating Organizational Citizenship Behavior (OCB) as a mediating construct within PT. Prasida Arta Begja Kamayangan. The study adopts an associative research framework, wherein primary data were elicited through self-administered questionnaires distributed among 75 personnel. The analytical outcomes disclose that organizational commitment manifests a statistically significant bearing on employee performance, whereas job satisfaction exerts no direct measurable influence, yet demonstrates a meaningful contribution to the enhancement of OCB. Additionally, OCB is found to exert a pronounced and favorable effect on performance outcomes. The investigation further substantiates that OCB functions as an intermediary conduit linking organizational commitment and organizational culture with employee performance, thereby reinforcing its pivotal role within organizational behavioral dynamics.